"100 Resilient Cities": Addressing Urban Violence and Creating a World of Ordinary Resilient Cities. Issue 7 (3rd October 2022) - Naef, Patrick
Abstract : Although the use of resilience in international relations and urban planning has given rise to a growing body of critical research, this contested concept continues to feature prominently in the conversation on the development of cities. Taking the 100 Resilient Cities (100RC) network pioneered by the Rockefeller Foundation as a case study, this article exposes some of the challenges inherent in the implementation of a global model of resilience. Exploring initiatives related to violence prevention in the member cities of Medellin, Cali (Colombia), Chicago (United States), and Belfast (Northern Ireland), this study will look at the practices of resilience officers, a position created by the 100RC network, and determine whether it can be considered as a new profession in the field of resilience planning. It will also use urban resilience to question the category of global cities, by suggesting that networks centered on resilience can serve as globalizing agents for "ordinary cities" (Robinson 2006 ). Finally, this article maintains that although the flexible and elusive definition promoted by 100RC facilitated a global circulation of the concept, its one-size-fits-all approach implied significant challenges and led in some cases to its depoliticization.